Multilingual modal sense classification using a convolutional neural network [Source code] - Marasović, Ana (Universität, 2019)
Abstract Modal sense classification (MSC) is aspecial WSD task that depends on themeaning of the proposition in the modal’s scope. We explore a CNN...
Kind of data: Program source code, python scripts
Production date: 2016
Gesehen am 09.10.2019
Keywords: Forschungsdaten; Datenbank